Integrated Education and the State of the Maliseet Language: Revitalization or Linguicide? - Nicholas, Andrea Bear (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1997)
This paper summarizes the results of a recent survey on the state of the Maliseet language in the Fredericton area, and correlates the statistics to the program of integrated schooling in New Brunswick. It then evaluates current Provincial educational policy using recent research on the effectiveness of education in the mother tongue both for the maintenance of a minority language and for the improvement of academic achievement levels in people of linguistic minorities.